Simultaneity of unhealthy behaviors associated with hypertension among Brazilian adults - Priscila Cristina Santos; Giovani Firpo Del Duca; Kelly Samara da Silva; Rafael Martins da Costa; Anne Ribeiro Streb; Aline Mendes Gerage; Debora Carvalho Malta (Revista Brasileira de Atividade Física e Saúde)
It is well known that some unhealthy behaviors are potentially associated with hypertension, but it is not known which combinations of simultaneous behaviors increase the chance of developing hypertension. In addition, more evidence is needed to assist in the development of preventive public policies in low- and middle-income countries. Thus, the objective was to determine the association between the clustering of four unhealthy behaviors and the occurrence of hypertension among Brazilian adults. The secondary data analyzed are derived from VIGITEL 2015 database, a cross-sectional national surveillance that included 35,548 adults aged 18 to 59 years living in Brazilian state capitals. Unhealthy behaviors and hypertension were measured by self-report. Sixteen combinations based on the presence and absence of the four unhealthy behaviors were performed and binary logistic regression was used to determine the association between simultaneity of these behaviors and hypertension. The odds to have all unhealthy behaviors were 3.50 (95%CI: 2.96 - 4.10) times higher than the expected value if unhealthy behaviors were independent. Adults with simultaneous all risk behaviors (OR = 2.42; 95%CI: 1.20 - 4.85), with excessive salt consumption and physical inactivity (OR = 1.41; 95%CI: 1.11 - 1.80) and with excessive alcohol consumption and physical inactivity (OR =1.60; 95%CI: 1.14 - 2.25) were more likely to have hypertension compared to the people without unhealthy behaviors. In conclusion, some combinations of unhealthy behaviors were actually more dangerous for hypertension in the investigated population. Future public policies to prevent hypertension can be more effective if to focus on simultaneity of unhealthy behaviors that increased the chance of developing the disease, especially physical inactivity.